Penerapan Aplikasi Mentari (Mental Health Remaja Indonesia) Assessment Pendeteksi Dini Kesehatan Mental Emosional Dan Perilaku Pada Remaja - Hertini, Reni; Rohita, Tita; Wibowo, Daniel Akbar; Muflihah, Muflihah; Oktavia, Suci Rahma; Lesmana, Indra (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Indonesia is a developing country with a fairly large number of mental sufferers. The prevalence of emotional mental disorders with symptoms of depression and anxiety in the population continues to increase so that the tendency to self-harm and suicide continues to increase. Suicide cases in Indonesia can reach 10,000 or the equivalent of every hour there is a suicide case Objective: Participants in this activity totaled 187 people with an age range of 12 to 15 years Method: implementation of the MENTARI assessment application on adolescent mental health Result: The results obtained after using the MENTARI application were that the majority of teenagers had emotional, behavioral and peer problems. Conclusion: Many things and conditions can cause pressure (stress) during adolescence. They are faced with various changes that are occurring within themselves as well as development targets that must be achieved according to their age.